2015
DOI: 10.1111/pan.12817
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient outcomes and satisfaction in pediatric population: data from the postoperative phone call

Abstract: A postoperative phone survey is cost-effective and appreciated by patients. We found that satisfaction with our perioperative services was not related to the rates of reported complications. Although reducing complications is of utmost importance, improvements in wait times and other operational issues would yield greater improvements in satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
0
21
0
2
Order By: Relevance
“…After the day of the operation, pain is known to persist in many children and some develop chronic pain . Pain in our survey was reported more frequently after some procedures, which points, clearly, to where there is potential for improvement and further audit.…”
Section: Discussionmentioning
confidence: 47%
“…After the day of the operation, pain is known to persist in many children and some develop chronic pain . Pain in our survey was reported more frequently after some procedures, which points, clearly, to where there is potential for improvement and further audit.…”
Section: Discussionmentioning
confidence: 47%
“…In a study evaluating the satisfaction of parents with the pediatric surgery patients, Brenn et al stated that the dissatisfaction reported by the parents was independent of the complication rate and was more because of the operational factors such as waiting times [24].…”
Section: Discussionmentioning
confidence: 99%
“…Features of the studies describing satisfaction measures and the dimensions of satisfaction are presented in Tables 1 and 2, and explored further in this article. Of the studies identified, six were the setting of elective procedures, 20‐25 while in eight studies this context was not specified 26‐33 . Six studies were in the context of general anesthesia 20,21,23‐26 while two also involved regional anesthesia 20,21 …”
Section: Satisfaction Measures In Contextmentioning
confidence: 99%
“…Tait et al used a combination of in‐hospital face‐to‐face interviews and phone calls 30 . Eight measures had high response rates (80–100%), 20,23‐28,30 whereas four had a response rate of <80% 21,29,31,32 . Two studies did not report their response rates 22,33 …”
Section: Satisfaction Measures In Contextmentioning
confidence: 99%